2019
DOI: 10.1155/2019/3293145
|View full text |Cite
|
Sign up to set email alerts
|

Hints for Genetic and Clinical Differentiation of Adult-Onset Monogenic Autoinflammatory Diseases

Abstract: Monogenic autoinflammatory diseases (mAIDs) are inherited errors of innate immunity characterized by systemic inflammation recurring with variable frequency and involving the skin, serosal membranes, synovial membranes, joints, the gastrointestinal tube, and/or the central nervous system, with reactive amyloidosis as a potential severe long-term consequence. Although individually uncommon, all mAIDs set up an emerging chapter of internal medicine: recent findings have modified our knowledge regarding mAID path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 221 publications
2
13
0
4
Order By: Relevance
“…As observed in other studies (136,141), we found that mutations with the lowest p-weighted scores (log(p w ) < −2, corresponding to p w < 0.01), which are expected to be the most severely-disruptive to NLRP3 structure and function, occur in the NACHT domain between Glu250 and Arg550 with a mutational hotspot including the Arg262 site ( Figure 2A). Arg262 is the most cited mutation site (17, 59-61, 64, 66, 69, 93, 96, 136), is shared between all CAPS, and has a wide variance of reported substitutions.…”
Section: Bioinformatics Tools Reveal Inverse Relationship Between CLIsupporting
confidence: 86%
“…As observed in other studies (136,141), we found that mutations with the lowest p-weighted scores (log(p w ) < −2, corresponding to p w < 0.01), which are expected to be the most severely-disruptive to NLRP3 structure and function, occur in the NACHT domain between Glu250 and Arg550 with a mutational hotspot including the Arg262 site ( Figure 2A). Arg262 is the most cited mutation site (17, 59-61, 64, 66, 69, 93, 96, 136), is shared between all CAPS, and has a wide variance of reported substitutions.…”
Section: Bioinformatics Tools Reveal Inverse Relationship Between CLIsupporting
confidence: 86%
“…Considering the heterogeneity of the clinical manifestations and the existence of overlapping phenotypes, early diagnosis of NLRP3 ‐AID is a big challenge for most physicians in real‐life scenarios as for other monogenic AIDs; thus, algorithms for the differential diagnosis of these conditions have been recently proposed [15]. In this study, we found that the duration of diagnosis delay was approximately 20 years, which indicated that NLRP3 ‐AID may be underdiagnosed in the Chinese population.…”
Section: Discussionmentioning
confidence: 79%
“…1) with a variable modality of recurrence, alternating with periods of complete wellness [2]. The description of tardive manifestations, veiled phenotypes and atypical clinical signs beginning in adulthood has been more and more reported in recent times for different AIDs, requiring that many specialists become confident with concepts, details and management of autoinflammation [3].…”
Section: Introductionmentioning
confidence: 99%